Exploring the Drivers of Intention to Use Interactive Whiteboards among Malaysia University Students: Does Technology Self-Efficacy Matter? - Wong, Kung-Teck; Muhammad, Mazura @ Mastura binti; Abdullah, Norazilawati binti (International Journal of Emerging Technologies in Learning (iJET), 2020)
The effective use of an interactive whiteboard (IWB) in teacher-education institutions depends strongly on student teachers’ intention of using it. Despite the recent surge in published research on the widespread applications for IWB in teaching and learning, few have developed a model to elucidate the elements which contribute to student teachers’ intention to use IWB. The aim of this study was to develop a model which demonstrates the variables that affect student teachers’ intentions and which also explain their interactions. The proposed IWB intention to use research model is based on prominent educational technology acceptance theories and models. Five variables (technology self-efficacy, performance expectancy, effort expectancy, social influence, and intention to use) were selected to build a model for this study. Structural Equation Modelling (SEM) was used for this study to identify the predictors and the model fit. The proposed model has accounted for 47.6% of the variance in the intention to use IWB.